The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18488/journal.aefr.2018.82.205.230
|View full text |Cite
|
Sign up to set email alerts
|

Does Bank Corporate Governance Matter for Bank Performance and Risk-Taking? New Insights of an Emerging Economy

Abstract: Article History JEL Classification:C2; E43; G21; G28; G34.This study empirically focuses on the effects of corporate governance on bank performance and risk-taking during the financial crisis of [2007][2008]. Using a balanced panel data in an emerging economy, we examine whether banks with corporate governance mechanism have heterogeneous effect on profitability and risk-taking amidst the crisis. Our empirical findings show that corporate governance derives benefits concerning profitability and risk-taking for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Table 7 shows that country governance variables have no impact on bank performance. Studies argue that governance variables can reduce bank risk and provide predictability (Moudud-Ul-Huq et al, 2018). Our results are consistent with the bank minority of bank performance literature and argue that country governance variables do not affect bank performance in emerging countries (Elmawazini and Khalid, 2017).…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Table 7 shows that country governance variables have no impact on bank performance. Studies argue that governance variables can reduce bank risk and provide predictability (Moudud-Ul-Huq et al, 2018). Our results are consistent with the bank minority of bank performance literature and argue that country governance variables do not affect bank performance in emerging countries (Elmawazini and Khalid, 2017).…”
Section: Empirical Results and Discussionsupporting
confidence: 90%
“…Table 7 shows that country governance variables have no impact on bank performance. Studies argue that governance variables can reduce bank risk and provide predictability (Moudud-Ul-Huq et al. , 2018).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Also, some variables or unobserved effects are not specified in the regression but subsumed in the stochastic disturbance term that affects both bank stability and competition, thus amounting to a correlation between the error term and competition measure. Therefore, to obtain unbiased and consistent estimates after addressing the issue of endogeneity (Moudud-Ul-Huq et al , 2018), we use a two-step system generalized method of moments (GMM) of Blundell and Bond (1998) with Windmeijer’s (2005) finite sample correction for dynamic panel data. We do not use the fixed effects estimation technique within our dynamic panel framework as it provides inconsistent and biased results for dynamic relationships (Dalwai et al , 2021; Goswami, 2021).…”
Section: Methodology and Datamentioning
confidence: 99%
“…According to the competition-fragility view, competition results in bank failures, which may destabilize various crucial macroeconomic indicators. By disrupting the payment system and interbank lending market, the effects of a shock to one bank have the potential to spread to other banks through contagion (Noman et al , 2017; Danisman, 2018; Moudud-Ul-Huq et al , 2018). As a result, researchers, policymakers and regulators have concentrated their efforts on identifying factors contributing to bank soundness.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the studies of Bhagat et al, 2011;Bhaumik and Selarka, 2012;Ding et al, 2013;Donou-Adonsou and Sylwester, 2017;Ernovianti and Ahmad, 2017;Etri et al, 2016;Nicholson and Salaber, 2013;Yusupov, 2012) found a positive relationship and (Aybar and Ficici, 2009;Bertrand and Betschinger, 2012;Bibi et al, 2018;Forssbaeck and Nielsen, 2016;Tomec and Jagrič, 2017) found negative relationship while (Adedeji et al, 2015;Liao and Williams, 2008) found no relationship between the two variables. Moreover, the previous empirical studies reported a strong relationship between corporate governance and bank's performance (Grassa and Matoussi, 2014;Hakimi et al, 2018;Huq et al, 2018;Pathan and Faff, 2013). The above observed inconsistent findings are what led to the introduction of corporate governance to moderate the relationship between recapitalization and the bank's performance.…”
Section: Introductionmentioning
confidence: 93%